COVID-19 and human resources for health: analysis of planning, policy responses and actions in Latin American and Caribbean countries - Juana Paola Bustamante Izquierdo; E. Benjamín Puertas; Diana Hernández Hernández; Hernán Sepúlveda (BMC, 2023)
Abstract Background The COVID-19 pandemic led to worldwide health service disruptions, due mainly to insufficient staff availability. To gain insight into policy responses and engage with policy-makers, the World Health Organization (WHO) developed a global approach to assess and measure the impact of COVID-19 on the health workforce. As part of this, WHO, together with the Pan American Health Organization (PAHO), supported an impact analysis of COVID-19 on health workers and policy responses, through country case studies in Latin America and the Caribbean (LAC). Methods We sought to identify lessons learned from policies on human resources for health (HRH) during health emergencies, to improve HRH readiness. First, we performed a rapid literature review for information-gathering. Second, we used the WHO interim guidance and impact measurement framework for COVID-19 and HRH to systematically organize that information. Finally, we used the Health Labour Market Framework to guide the content analysis on COVID-19 response in eight LAC countries and identify lessons learned to improve HRH readiness. Results Planning and implementing the COVID-19 response required strengthening HRH governance and HRH data and information systems. The results suggest two main aspects for HRH governance crucial to enabling an agile response: (1) aligning objectives among ministries to define and produce regulation and policy actions; and (2) agreeing on the strategy for HRH management between the public and private sectors, and between central and local governments. We identified three areas for improvement: (a) HRH information systems; (b) methodologies to estimate HRH needs; and (c) teams to analyse information for decision-making. Three key actions were identified during countries monitored, reviewed, and updated their response stages: (i) strengthening response through primary health care; (ii); planning HRH needs to implement the vaccination plan; and (iii) securing long-term HRH availability. Conclusion Countries coordinated and articulated with different stakeholders to align objectives, allocate resources, and agree on policy actions to implement the COVID-19 response. Data and information for HRH preparedness and implementation were key in enabling an agile COVID-19 response and are key areas to explore for improved pandemic preparedness.